Novel organic repellent for leaf-cutting ants: tea tree oil and its potential use as a management tool. Issue 1 (2nd January 2021) - Buteler, Micaela; Alma, Andrea Marina; Herrera, María Laura; Gorosito, Norma B.; Fernández, Patricia Carina
Abstract: Leaf-cutting ants are insects of great economic importance which cause economic losses in numerous crops. Compounds that modulate behaviour, and among these natural repellents, show promise in integrated pest management strategies. Tea tree oil has been found to be repellent to certain insect pests, so this study aimed at identifying the effect of tea tree on foraging behaviour in Acromyrmex spp. ants in laboratory as well as in field trials. In laboratory bioassays, a repellent dose response effect of tea tree oil was observed, where concentrations of 0.0001 to 0.1% tea tree did not affect ant behaviour, but concentrations of 1 and 10% repelled ants. In the laboratory, the repellent effect of tea tree was lost after four days and its effect on ant behaviour was evident only at very short distances (less than 1 cm). In the field, ants avoided walking through filter papers treated with tea tree at 1% placed on the foraging trails, and food resources surrounded by tea tree at 1% were not collected. Tea tree is a potent short term leaf-cutting ant repellent and attractive food sources could be protected from leaf-cutting ants attack by this oil.